Oral Cyclophosphamide for Patients With Metastatic Castration-Resistant Prostate Cancer in a Scenario of Limited Health Care Resources - Diana del Cisne Pineda; Gabriel Berlingieri Polho; Yumi Ricucci Shinkado; Gustavo Alves Contado; Nathalia de Souza Crusoe; Vivian Naomi Horita; Joao Carlos Resende; Jamile Almeida Silva; Guilherme Fialho de Freitas; David Queiroz Muniz; Caio V. Suartz; Leopoldo Alves Ribeiro-Filho; et al. (JCO Global Oncology)
PURPOSEPrior noncontemporary studies showed that oral cyclophosphamide is an active treatment of metastatic castration-resistant prostate cancer (mCRPC). However, cyclophosphamide is currently underutilized in routine clinical practice given the lack of survival benefit and the emergence of more effective treatments.METHODSWe retrospectively reviewed our institutional database to identify patients with mCRPC treated with cyclophosphamide. Prostate-specific antigen decrease ≥50% from baseline (PSA50) response was determined as the proportion of patients achieving a prostate-specific antigen (PSA) decline ≥50% from baseline. Radiographic responses and progression were evaluated by Prostate Cancer Working Group 3. Survival estimates used the Kaplan-Meier method, and correlations were made with Chi-square test for categorical variables.RESULTSFrom January 2011 to January 2023, 341 patients with mCRPC received oral cyclophosphamide at a tertiary cancer center in São Paulo, Brazil. The most common regimen (95%) was 100 mg once daily 21 days on, 7 days off. At prostate cancer diagnosis, the median age was 64.4 years (IQR, 59.4-70.8), 61.9% had metastatic de novo disease, and 55.5% had Gleason ≥8. The median number of previous treatment lines was three (IQR, 2-4). Any PSA decline was observed in 33.4%, and 13.2% had a PSA50 response. Median response duration was 2.1 months (IQR, 1.4-3.8). Ten patients (3%) were treated for ≥1 year. PSA50 response was associated with no prior docetaxel use and Eastern Cooperative Oncology Group performance status 0 or 1.CONCLUSIONOral cyclophosphamide is a feasible treatment option for patients with mCRPC, particularly in a scenario of limited health care resources.